Direct hospital costs of total laparoscopic hysterectomy compared with fast‐track open hysterectomy at a tertiary hospital: a retrospective case‐controlled study. (2nd May 2013) - Rhou, Yoon J.J.; Pather, Selvan; Loadsman, John A.; Campbell, Neil; Philp, Shannon; Carter, Jonathan
Abstract : Aims: To assess the direct intraoperative and postoperative costs in women undergoing total laparoscopic hysterectomy and fast‐track open hysterectomy. Methods: A retrospective review of the direct hospital‐related costs in a matched cohort of women undergoing total laparoscopic hysterectomy (TLH) and fast‐track open hysterectomy (FTOH) at a tertiary hospital. All costs were calculated, including the cost of advanced high‐energy laparoscopic devices. The effect of the learning curve on cost in laparoscopic hysterectomy was also assessed, as was the hospital case‐weighted cost, which was compared with the actual cost. Results: Fifty women were included in each arm of the study. TLH had a higher intraoperative cost, but a lower postoperative cost than FTOH (AUD$3877 vs AUD$2776 P  < 0.001, AUD$3965 vs AUD$6233 P  < 0.001). The total cost of TLH was not different from FTOH (AUD$7842 vs AUD$9009 P  = 0.068) and after a learning curve; TLH cost less than FTOH (AUD$6797 vs AUD$8647, P  < 0.001). The use of high‐energy devices did not impact on the cost benefit of TLH, and hospital case‐weight‐based funding correlated poorly with actual cost. Conclusion: Despite the use of fast‐track recovery protocols, the cost of TLH is no different to FTOH and after a learning curve is cheaper than open hysterectomy. Judicious use of advanced energy devices does not impact on the cost, and hospital case‐weight‐based funding model in our hospital is inaccurate when compared to directly calculated hospital costs.